Physiological Load and Psychological Stress During a 24-hour Work Shift Among Finnish Firefighters. Issue 1 (January 2017) - Kaikkonen, Piia; Lindholm, Harri; Lusa, Sirpa
Abstract : Objective: The aim of this study was to describe physiological load and psychological stress of Finnish firefighters during a 24-hour work shift. Methods: R-R intervals were recorded during 24-hour work shifts. Short-time Fourier transform was used to analyze heart rate variability during shifts. Results: HRmean, HRpeak, and square root of the mean of the sum of the squares of the differences between adjacent R-to-R peak intervals of the 24-hour shift was 73 ± 7 bpm (38 ± 4% of HRmax ), 156 ± 16 bpm (82 ± 8% of HRmax ), and 42 ± 14 ms. Mean VO2 was 11 ± 2 (% of VO2max ) and VO2peak 72 ± 11 (% of VO2max ). Conclusions: Physiological load and psychological stress were temporarily high, even in young, fit firefighters. As the relative work load may increase and recovery processes slow down among aging employees, fatigue may occur unless work arrangements are well-designed.